2020
DOI: 10.1111/jfpp.15034
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activities of fennel ( Foeniculum vulgare Mill.) essential oils and ethanolic extracts of conventional and organic seeds

Abstract: Essential oils and ethanolic extracts of seeds of seven organically and conventionally grown accessions (E1, E2, E3, E4, E5, E6, and E7) of fennel (Foeniculum vulgare Mill.) were examined for their chemical constituents, antioxidant and antibacterial activities. Accession E7 presented the highest essential oil yields of 4.30 ± 0.45 and 3.24 ± 0.46%, respectively, for organic and conventional mode. However, E6 noted the lowest ethanolic extract yield in the two modes of cultivation. Gas chromatography/mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…A previous study reported the value of TFC carrot extract (20.48 ±28 mg QE/g) dry weight material (Nadeem et al, 2018). Some recent studies have also shown that the decrease in TFC during thermal processing is particularly associated with the extraction technique, time of processing, and solvent used (Khammassi et al, 2022;Ben Abdesslem et al, 2021). This study was in strong evidence with the study conducted on the basil seeds that determined the effect of boiling temperature (>100 o C) on the TFC and TPC.…”
Section: Flavonoid Contents In Different Candy Treatmentssupporting
confidence: 72%
“…A previous study reported the value of TFC carrot extract (20.48 ±28 mg QE/g) dry weight material (Nadeem et al, 2018). Some recent studies have also shown that the decrease in TFC during thermal processing is particularly associated with the extraction technique, time of processing, and solvent used (Khammassi et al, 2022;Ben Abdesslem et al, 2021). This study was in strong evidence with the study conducted on the basil seeds that determined the effect of boiling temperature (>100 o C) on the TFC and TPC.…”
Section: Flavonoid Contents In Different Candy Treatmentssupporting
confidence: 72%
“…In the struggle for the development of all human civilizations, there has always been a close and shoulder-to-shoulder relationship between man and plants. Due to the proven antimicrobial effects of various medicinal plants in numerous studies, drug resistance caused by pathogens, and side effects of chemical antimicrobials, the approach of scientific research to natural resources has increased greatly in recent decades (33,34). On the other hand, the results of this study suggest that thyme (T. vulgaris L.) can be used to treat infections caused by B. cereus.…”
Section: Discussionmentioning
confidence: 86%
“…Potentially, several industrial applications,using fennel seed powder or FEO, could be carried out based on present work results in addition to our previous studies. For instance, the cultivar Cv2 was rich in sugars (61%), in transanethole (72.73%) (Ben Abdesslem et al, 2020) and β-carotene (0.647 mg/mg DM) that are considered of high interest in diets nowadays.…”
Section: Photosynthetic Parameters Of Fennel Seedsmentioning
confidence: 99%
“…On the other hand, cultivar Cv6 with a considerable nutritional composition, in addition to its richness in chlorophyll (0.584 mg/mg DM) and β-carotene, as well as its essential oil with high content of trans-anethole (66.73%), could be considered for the preparation of a tea using dried seeds (Saber and Eshra, 2019). Moreover, cultivar Cv1 had a high content of phenolic compounds and a very effective antibacterial activity against Staphylococcus aureus, listeria monocytogenes and Esherichia coli (Ben Abdesslem et al, 2020). Also, essential oil of cultivar Cv1 was shown to have a high content of methyl-chavicol (76.29%) (Ben Abdesslem et al, 2020).…”
Section: Photosynthetic Parameters Of Fennel Seedsmentioning
confidence: 99%
See 1 more Smart Citation